Mối quan hệ giữa dòng vốn bên ngoài và hành vi đầu tư của doanh nghiệp dưới sự tác động của chính sách tiền tệ tại Việt Nam - Lai Trung , Thanh; Nguyen Quang , Binh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2018)
This research aims to investigate the effect of external capital flow on investment behavior of 625 non-financial listed firms in Vietnam’s Securities Market from 2000–2016 period. The result shows that the investment behavior is mainly financed by internal funds. Besides, the research also examines the effect of monetary policy on the relationship between external funds and business investment behavior. The result indicates that the credit channel of monetary policy is likely not keeping the main role for supplying capital for business due to the incomplete development of the financial market and the banking system as well as the difficulties of economic crisis.